OPTIMIZATION OF LOCATION MODEL OF CAPACITATED NETWORK - Sutanto Soehodho; Nahry Nahry (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2011)
This study concerns with the research work on Location Model of Public Service Obligation State-Owned Company (PSO-SOC). Its aim is to develop an approach of making location decision on distribution facilities of such company, in which capacities of facilities are limited (capacitated facilities) and it deals with single commodity. Heuristic solution is proposed to modify established Add Algorithm, which is designed for uncapacitated facilities. The Network Representation is used to represent original problem of LocationModel. An example is provided to illustrate the proposed step-wise of solving the model.Keywords: location model, Add Algorithm, Network Representation.